2013
DOI: 10.1074/jbc.m112.392050
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves Cardiomyopathy in Dystrophin-deficient Mice through SIRT1 Protein-mediated Modulation of p300 Protein*

Abstract: Background: Dystrophin deficiency leads to life-threatening cardiomyopathy, whereas cardiac p300 promotes cardiac hypertrophy/failure. Results: The SIRT1 activator resveratrol inhibited p300 protein up-regulation and attenuated cardiomyopathy in dystrophindeficient mice, and SIRT1-induced p300 down-regulation was mediated via its deacetylation and ubiquitination. Conclusion: SIRT1 activation ameliorates dystrophic cardiomyopathy by targeting p300. Significance: Negative regulation of p300 is a novel cardioprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 30 publications
(20 reference statements)
3
83
0
Order By: Relevance
“…31,32 Moreover, the administration of RSV, a specific SIRT1 activator, suppressed cardiac hypertrophy and restored cardiac function, suggesting that SIRT1 is essential for cardiomyocyte development. 33,34 Previous studies showed that JNK activation influences SIRT1 protein stability, 24,25 consistent with our observations. We found that a JNK1/2 activator (anisomycin) promoted SIRT1 degradation via the ubiquitinproteasome system.…”
Section: Discussionsupporting
confidence: 82%
“…31,32 Moreover, the administration of RSV, a specific SIRT1 activator, suppressed cardiac hypertrophy and restored cardiac function, suggesting that SIRT1 is essential for cardiomyocyte development. 33,34 Previous studies showed that JNK activation influences SIRT1 protein stability, 24,25 consistent with our observations. We found that a JNK1/2 activator (anisomycin) promoted SIRT1 degradation via the ubiquitinproteasome system.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have shown that NO donation 45,46 or antioxidant therapy 47,48 has beneficial effects in the mdx mouse models. For example, restoration of the NO-cGMP pathway 3,49,50 with phosphodiesterase-5 inhibitors, such as sildenafil, improved cardiac pathology in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…RSV administration exerts beneficial effects against cardiovascular and neurodegenerative diseases [4]. We previously showed that RSV retards the progression of chronic heart failure in cardiomyopathic TO2 hamsters [13] and suppresses the skeletal and cardiac muscle pathologies in dystrophin-deficient mdx mice, a model of Duchenne muscular dystrophy [14], [15]. Such beneficial effects are thought to be at least partly attributable to the increased SIRT1 activity [11], [13][15].…”
Section: Introductionmentioning
confidence: 99%